Whistling past the graveyard eaudiobook - Crandall, Susan (Dreamscape Media, 2013)
In the summer of 1963, nine-year-old spitfire Starla Claudelle runs away from her strict grandmother's home. Mamie is the nearest thing to family Starla has. After being put on restriction yet again for her sassy mouth, Starla is caught sneaking out. She fears Mamie will make good on her threat to send Starla to reform school, so Starla walks to the outskirts of town, and just keeps walking. Walking a lonely country road, Starla accepts a ride from Eula, a black woman traveling alone with a white baby. The trio embarks on a road trip that will change Starla's life forever. She sees for the first time life as it really is - as she reaches for a dream of how it could one day be.